Analisis Program Monetisasi Youtube Menurut Hukum Ekonomi Syariah - Nur Arbaien, Muhamad Fasya; Nurhasanah, Elis (Al-Muamalat: Jurnal Ekonomi Syariah, 2023)
YouTube is an application that has many benefits so it can be used as a medium to find various available information. Many people are looking for money or income through YouTube by registering their YouTube account with monetization from Google AdSense. This research is motivated because the author sees many people who do not know the laws of YouTube monetization according to Islamic law. The method used is a descriptive method with a qualitative approach. The source of data in this study is secondary data. The data collection technique used is library research. The data analysis technique is carried out with a content analysis model by conducting research that is an in-depth discussion of the contents of written information. After that, the researcher interprets the existing data to draw conclusions after conducting research on all the data that will answer the problems in the study. From the results of this study, it can be concluded that the YouTube monetization program is not in accordance with Islamic law. This is due to the Revenue per Mille Impression policy when the distribution of ratios does not have clear proportions that regulate profit sharing for both parties. Therefore, it is necessary to realize the syirkah contract in the monetization program. With the implementation of the syirkah contract, the two parties will know things that are forbidden by IslamYoutube merupakan aplikasi yang memiliki banyak manfaat dan dapat digunakan untuk mencari berbagai informasi yang tersedia. Banyak orang yang mencari penghasilan melalui Youtube dengan cara melakukan kerja sama dengan program monetisasi. Tujuan penelitian ini adalah untuk mengetahui hukum monetisasi youtube dalam perspektif hukum ekonomi syariah. Metode yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Berdasarkan penelitian penulis, , program monetisasi youtube tidak sesuai dengan syariat Islam. Hal ini disebabkan oleh kebijakan Revenue per-Mille Impression, pada saat pembagian nisbah tidak adanya persentase secara jelas yang mengatur pembagian keuntungan kedua belah pihak. Dengan demikian dalam monetisasi Youtube ini perlu mengimplementasikan akad syirkah, agar kedua belah pihak dapat mengetahui hal-hal yang dilarang menurut hukum ekonomi syariah. Kesimpulannya, program monetisasi Youtube tidak sesuai dengan prinsip -prinsip syariah.